حوكمة الموارد البشرية وسياسة التوظيف في المؤسسات الاستشفائية: دراسة حالة المستشفى الجامعي تلمسان - حموم, سعاد; بونوة, شعيب (جامعة الوادي - University of Eloued, 2022)
جاءت هذه الدراسة لتسليط الضوء على دور حوكمة الموارد البشرية كمدخل لتعزيز مقومات التوظيف الجيد من خلال معايير الحوكمة في المؤسسات الاستشفائية. ومن أجل تحقيق أهداف الدراسة تم تصميم إستبانة وزعت على موظفي المركز الاستشفائي الجامعي-تلمسان-بحيث تم توزيع (43) إستبانة واسترجع منها (33). وخلصت الدراسة إلى وجود علاقة ايجابية لكنها متوسطة بين حوكمة الموارد البشرية وسياسة التوظيف في المؤسسة الاستشفائية لولاية تلمسان. هذا ما عكسته معاملات الارتباط التي أتت متوسطة بالاضافة إلى أن عملية التوظيف تخضع نسبيا لبعض الممارسات البيروقراطية التي أثرت سلبا على مبدأ المساواة للالتحاق بالوظيفة العمومية This study came to shed light on the role of human resource governance as an entry point to enhance the elements of good employment through governance standards in hospital institutions. In order to achieve the objectives of the study, a questionnaire was designed and distributed to the employees of the University Hospital Center -Tlemcen - so that (43) questionnaires were distributed and (33) were received. The study concluded that there is a positive but moderate relationship between human resource governance and employment policy in the hospital institution of the state of Tlemcen. This was reflected in the correlation coefficients that came as average, in addition to the fact that the recruitment process is relatively subject to some bureaucratic practices that negatively affected the principle of equality to join the public office
Human resource governance and employment policy in hospital Institution: a case study of the University Hospital of Tlemcen
مقال
Keywords: حوكمة الموارد البشرية ; التوظيف ; الحوكمة ; المؤسسات الاستشفائية